Advancements in Characterization of Ancient Potteries from Southeast Asia: A Review of Analytical Techniques - Sirisathitkul, Chitnarong (Makara Journal of Science, 2024)
Ancient potteries offer valuable information regarding technological advancements, life dynamics, cultural diversity, and trade routes in the past. Earthenware, stoneware, and porcelain from Southeast Asia have been characterized using several analytical techniques, as reviewed in this article. Fluorescent and diffracted X-rays give rise to elemental and phase compositions, respectively. Examination of molecular bonds requires vibrational spectroscopy, which is useful for the identification of organic materials in ancient potteries. With the advent of portable X-ray fluorescence and Raman spectrometry, on-site analysis of archeological ceramics is now possible. For in-depth analysis, synchrotron light sources can provide new insights into artifacts through X-ray and vibrational spectroscopies using elaborate setups. Synchrotron X-ray absorption specifically reveals local atomic structures within artifacts. Charged particles and neutrons are increasingly used as a source of atomic excitation, which improves the depth analysis of artifacts. The obtained elemental composition and mineral phases reveal the origin and production of potteries. Insights into production techniques and firing conditions can be obtained. In addition, the trade routes and networks in ancient Southeast Asia can be established on the basis of archeological ceramic analyses.